Sistem Informasi Geografis (Geog Implementasi Algoritma Floyd-Warshall Menentukan Rute Terpendek Pada Pencarian Lokasi Petani Beras - dhiafakri, Resti (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2024)
This research was conducted with the aim of finding out how to implement the shortest route using the Floyd-Warshall method and to analyze how much influence the implementation of the Floyd-Warshall method has on finding the closest route to the location of the farmers that the author will study is located in Ladongi District, East Kolaka Regency. The Floyd-Warshall algorithm is one of the algorithms that can be used to solve the shortest route problem and is the easiest to implement because it can find all the shortest routes between every possible pairing of positions and is part of a dynamic program which is very efficient in solving optimal route problems. The Floyd-Warshall algorithm works by comparing every possible path in the graph for each pair of nodes and checking the resulting combination of nodes. The problem with the shortest route in everyday life is finding the location of farmers who provide rice stocks. The area which is known for having a lot of rice crops is Ladongi District, East Kolaka Regency. Some things that must be prepared in the search for farmer locations are finding effective ways to reach farmer locations because it can save energy and costs and can make it easier for people to get farmer locations.